Comparison of labour and postnatal satisfaction between women with and without severe maternal morbidity: a double-cohort study - Mohd Noor Norhayati; Adnan Fatin Imtithal; Yunus Nor Akma (BMJ Open, 2022)
Objective To compare labour and postnatal satisfaction between women with and without severe maternal morbidity in a tertiary hospital in Kelantan, Malaysia.Design A prospective double-cohort study.Setting Hospital and community based.Participants Women at childbirth and 1-month post partum.Outcome measures Labour satisfaction measured using the Malay version of the Women’s Views of Birth Labour Satisfaction Questionnaire and postnatal satisfaction measured using the Malay version of the Women’s Views of Birth Postnatal Satisfaction Questionnaire.Results A total of 198 participants responded following childbirth, while 193 responded 1-month post partum. Accordingly, although no significant difference in labour satisfaction scores following childbirth was observed between women with and without severe maternal morbidity, a significant difference in postnatal satisfaction score 1-month post partum had been noted (adjusted mean difference [95% CI]: 3 [0.54 to 5.45]; p=0.019). Moreover, domains for nursing a baby (0.08 [0.024] vs 0.06 [0.029]; p=0.022) and professional support (0.03 [0.022] vs 0.03 [0.029]; p=0.023) differed significantly between women with and without severe maternal morbidity.Conclusions Healthcare professional support and nursing of babies influenced the relationship between satisfaction and severe maternal morbidity during the later postpartum period.